ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP RETURN AWAL - Sastaviana, Lefti Claudya; Fatmaningrum, Erni Suryandari (Journal of Accounting and Investment, 2009)
This research is aimed to analyze of factors that influence the initial return. The factors are size of company, earning per share, return on asset, degree of leverage, age of company, ownership proportion of previous shareholder, auditor reputation, underwriter reputation, and price earning ratio. The sample for this research are 55 manufacturing and non manufacturing companies that have Initial Public Offering in Indonesian Stock Exchange from 2002-2008. Technique of collecting sample is purposive sampling. Multiple regression analysis was used to test the hypothesis. The results indicated that earning per share and underwriter reputation influences on initial return. Whereas size of company, return on asset, degree of leverage, age of company, ownership proportion of previous shareholder, auditor reputation, and price earning ratio do not influence on initial return.Â